Perception and intention to practice breastfeeding in adolescents in northeastern Mexico - Castro Sánchez, Ana Elisa; Ávila Ortiz., María Natividad; Zambrano Moreno, Adriana; Núñez Rocha, Georgina Mayela (Horizonte Sanitario, 2022)
Objective: To analyze the perception and intention to practicebreastfeeding (BF) in adolescents of both genders who have not yetbeen parents.Material and Methods: This was a qualitative study based ongrounded theory with empirical saturation. Twenty-one semi-structuredinterviews were conducted with students between 15 and 18 years ofage in preparatory schools in Monterrey, Nuevo León, Mexico.Results: Four patterns on the perception and intention of practicingbreastfeeding were identified: traditional; undecided; rejection; andegalitarian.Conclusions: The intention to support or practice BF is related togender identities and the project of having children and / or a personallabordevelopment project. There is convergence between differentperceptions and intentions to practice BF in the future, which aims toreview policies in this area.Keywords: Breastfeeding, adolescents, qualitative research, grounded theory.